FACTORS ASSOCIATED WITH KNOWLEDGE OF WARNING SIGNS AMONG PREGNANT WOMEN IN THE THIRD TRIMESTER AT THE “C” COMMUNITY HEALTH CENTER IN TANGERANG REGENCY, OCTOBER–DECEMBER 2025 - Siti Maisaroh (Yayasan Education and Social Center, 2025)
Accidental sampling with the Slovin formula was as many as 100 pregnant female respondents. The analysis was used univariate and bivariate with Chi-square statistical test. Results: bivariate analysis there was a relationship between age P-Value value 0.001, education P-Value 0.016, work P-Value 0.006, P-Value parity 0.000, and exposure to P-Value 0.021 information on pregnant women's knowledge about the danger signs of pregnancy in the third trimester at Puskesmas C Tangerang Regency in 2025 P-Value = P<a 0.05. Conclusion: from this study, there is a relationship between age, education, occupation, parity and information exposure with pregnant women's knowledge of pregnancy danger signs at Puskesmas C Tangeang Regency in 2025. The suggestion of this research is to further add a broader insight into the importance of having knowledge and understanding of danger signs in pregnant women.